DIASPORA-INDONESIAN LITERATURE WORKS OF INDONESIAN IMMIGRANTS IN AMERICA IN THE 2010s - Adji, Peni; Mulyani, Sri; Rosiandani, Ni Luh Putu (Sanata Dharma University, 2018)
Diaspora literature studies have been extensively conducted in the world of literature. However, Indonesian diaspora literature has not been conducted widely in the Indonesian literature studies. To begin with, this study will examine the diaspora literature written by Indonesian immigrants in America in the 2010s. The first genre of Indonesian diaspora literature by Indonesian immigrants in America in the 2010s includes the history novel, Only a Girl: Menantang Phoenix (by Lian Gouw) which talks about the history of Chinese society in the Dutch-Indonesian era until the Indonesian independence and Candik Ala 1965 (by Tinuk R. Yampolsky) which tells the history of G/30/S/PKI. The second is the short story genre, which is Mantra Maia (by Sofie Dewayani) and the third are memory stories, which is This is America, Beibeh (by Dian Nugraheni) both of which raise the issue of Indonesian migrant communities in America. Diaspora problems are always related to the identity construction. The identity in Only a Girl: Menantang Phoenix is the migratory tendency and avoidance of racial conflicts inherent in Chinese people, who migrated to Indonesia, and who eventually migrated to America. The identity in Candik Ala 1965 is the Indonesian political migrant in America who position themselves as the victims of violence in the Suharto regime. The identity contained in the Mantra Maia short stories collection is a new world (America) that makes the migrants experience the psychological tension between success and failure of adaptation. The identity depicted in the memory stories of This is America, Beibeh is the identity of the Indonesian migrants who are able to adapt positively, by always comparing their new experiences with their old experiences in Indonesia.DOI:https://doi.org/10.24071/ijhs.2018.010201